Local-global neural networks: a new approach for nonlinear time series modelling - Mayte Suarez Fari\~nas; Carloe E. Pedreira; Marcelo C. Medeiros (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2003)
In this paper, the Local Global Neural Networks model is proposed within the context of time series models. This formulation encompasses some already existing nonlinear models and also admits the Mixture of Experts approach. We place emphasis on the linear expert case and extensively discuss the theoretical aspects of the model: stationarity conditions, existence, consistency and asymptotic normality of the parameter estimates, and model identifiability. A model building strategy is also considered and the whole procedure is illustrated with two real time-series.
Keywords: 330; neural networks; nonlinear models; time-series; model identifiability; parameter estimation; model building; sunspot number.; Neuronale Netze; Zeitreihenanalyse; Theorie